Identifikasi Sistim Produksi dan Keragaan Produktivitas Domba Ekor Gemuk di Kabupaten Brebes Propinsi Jawa-Tengah - Akhmad Sodiq (Agricultural Faculty, 2010)
Identification of production system and productivity level of fat tailed sheep in brebes regency of central javaABSTRACT. Reproductive performance is one of the main determinants of productivity of the sheep. This applies to the breeding of animal for meat production. High reproduction rates are essential for profit in meat sheep production and determined by the number of progeny delivered in a given period of time. The level of reproductive performance is dependent on the interaction of genetic and environmental factors. The evaluation of reproductive performance of a local and adapted breed of sheep such as Fat Tailed Sheep can provide important information to understand its productive potential under local production system. The study was designed to identify characteristic of production system and to find out the level productivity of Fat Tailed Sheep in Brebes areas of Central Java. Livestock On-Farm Trials (LOFT) using multistage sampling was implemented in this study. Descriptive and variance analysis using procedure of General Linear Model (GLM) was applied in this study. This study revealed that (1) In general, production system in Brebes is based on integration scheme of crop livestock in the form of traditional smallholders. In low land area, mostly extensive and tethering model were implemented. Intensive and semi intensive model was found in landless area. (2) Average litter size at birth was 1.54 head and dominated by double litter, followed by single and triplets (46.8, 47.88 and 4.29%). The highest preweaning lamb mortality was 15% with the average 8.9%. Ewe productivity ranges from 1.76-5.24 with average of 2.14 lamb/ewe/year. Least squares analysis of variance reveals that ewe reproduction rate was significantly affected by type of birth.